SUDDEN DEATH OF A COCAINE BODY PACKER: A CASE REPORT FROM DELHI, INDIA (Journal of Forensic Medicine & Toxicology, 2013)
A 42 year old male, Nigerian national, was brought dead to emergency care of a hospital in Delhi. At autopsy three cocaine filled polythene pouches, one of which found burst were present inside the stomach of the deceased. The cause of death was opined as acute cocaine overdose. Though few cases of death in cocaine body packer have been reported worldwide, the present case is the first such case reported from India.
Keywords: Body packer; Cocaine; Trafficking